Edukasi Tanggap Bencana Melalui Kegiatan Sosialisasi Guna Mewujudkan Masyarakat Desa Pijot Yang Tangguh - Dipo Ario Kusuma; Siti Maryam Ulfa; Arni Emiza Febrianti; Rosiatul Ismi; Siti Nuriah; Nurul Zainiyah; Rina Nuranjanisa; Soraya Rosanti; Ni Komang Eva Yuniasih; Tiara Hesti Amanda; Mila Andara; Lalu Sumardi (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Pijot Village is administratively one of 15 villages in Keruak District which is located at a radius of 3 Kilometers east of the capital city of Keruak District. Pijot Village has 715 hectares of area, which is spread over 8 Hamlet Heads, with a total population of 6.113 people in Pijot Village. The large number of residents and the location of the area on the coast with a height of 500 meters above sea level and a rainfall level of 491 mm. The condition of Pijot Village which is geographically, geologically, hydrologically and demographically prone to disasters with a fairly high frequency, as well as the fact that public awareness and knowledge is minimal in carrying out disaster management. For this reason, the public servant need to embedded special understanding and learning into the community through socialization activities for emergency response. The purpose of this activity is that the community has knowledge related to disaster management and will be always ready when a disaster occurs which can happen at any time, so as to realized a resilient and disaster-responsive Pijot Village community.